2015
DOI: 10.1111/febs.13499
|View full text |Cite
|
Sign up to set email alerts
|

Human cathepsin L, a papain‐like collagenase without proline specificity

Abstract: Several members of the papain-like peptidase family have the ability to degrade collagen molecules by cleaving within the triple helix region of this difficult substrate. A common denominator of these peptidases is their ability to cleave substrates with Pro in the P2 position. In humans, cathepsin K is the best-known papain-like collagenase. Here, we investigate the collagenolytic activity of human cathepsin L, which is closely related to cathepsin K. We show that, despite lacking proline specificity, catheps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 46 publications
(76 reference statements)
0
7
1
Order By: Relevance
“…Siponen et al () have recently shown by immunohistochemical analyses that CatK is expressed by melanocytes and macrophages, and sporadically in basal keratinocytes and endothelial cells, and that small amounts of CatK also exist extracellularly as well as intracellularly. Given that CatK has powerful collagenolytic activity, it is possible that it is mainly responsible for the degradation of extracellular matrix components such as collagens and elastin (Novinec and Lenarcic, ; Korenc et al , ). Another study showed that the expression levels of CatK in human dermal fibroblasts are upregulated by ultraviolet A radiation, suggesting that CatK may be involved in intracellular elastin degradation and contributes to solar elastosis (Xu et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Siponen et al () have recently shown by immunohistochemical analyses that CatK is expressed by melanocytes and macrophages, and sporadically in basal keratinocytes and endothelial cells, and that small amounts of CatK also exist extracellularly as well as intracellularly. Given that CatK has powerful collagenolytic activity, it is possible that it is mainly responsible for the degradation of extracellular matrix components such as collagens and elastin (Novinec and Lenarcic, ; Korenc et al , ). Another study showed that the expression levels of CatK in human dermal fibroblasts are upregulated by ultraviolet A radiation, suggesting that CatK may be involved in intracellular elastin degradation and contributes to solar elastosis (Xu et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…36 However, CatCΔEx does not cleave intact collagen ( Figure 4D), whereas cathepsin L, which lacks proline specificity does. 28 Therefore, the relation between collagenolytic activity and proline specificity is not straight forward. CatCΔEx has significantly lower kcat values for the hydrolysis of synthetic substrates than other cysteine cathepsins 35 and consequently kcat/Km values are 1 or 2 orders of magnitude lower in comparison to the dipeptidyl-peptidase activity of cathepsin C. 37 Nevertheless, kcat values in this order of magnitude are not unusual for proteolytic enzymes and similar values have recently been determined for the papain-like protease responsible for cell death in the plant N.benthamiana.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless after the prolonged incubation (40 minutes) CatCΔEx was able to completely degrade gelatin into small fragments not observable on the SDS-PAGE (not shown). Native type I collagen, on the other hand, is a tough substrate for proteases that is successfully degraded by cathepsin K and in weaker manner by cathepsin L. 19,28 Samples of native type I collagen incubated with CatCΔEx showed no detectable collagenolytic activity of the protease ( Figure 4D).…”
Section: Degradation Of Macromolecular Substratesmentioning
confidence: 99%
“…The interplay among human cathepsins in the physiopathology processes is observed for CatL, which plays a role in the collagenolytic activity, despite lacking proline specificity required for this activity. The CatL activity resulted in cleavage of type I collagen within the triple helix region of collagen-like CatK, even though CatL is 4-fold less potent …”
Section: Cathepsin Kmentioning
confidence: 99%